Pengaruh Kompensasi Dan Disiplin Kerja Terhadap Kinerja Karyawan (Sensus Pada Bengkel Per Mobil Cahya Fajar Magelang) - Sarah Munparidah; Kusuma Agdhi Rahwana; Barin Barlian (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims to determine the effect simultaneously and partially of Compensation and Work Discipline on Employee Performance at the Cahya Fajar Car Repair Shop, Magelang. The research method used in this study is to use quantitative research methods with a census approach. The population in this study were 44 employees of the Cahya Fajar Car Repair Shop. The type of data used in this study is primary data obtained through questionnaires. The data testing technique used in this study uses the validity test, reliability test and classic assumption test. Data analysis in this study used multiple regression analysis using SPSS software version 25. The results of the study show that compensation and work discipline simultaneously have a significant effect on employee performance at the Cahya Fajar Magelang Car Workshop. Partial compensation has a significant effect on employee performance at the Cahya Fajar Car Repair Shop, Magelang. Work Discipline partially has a significant effect on Employee Performance at the Cahya Fajar Car Repair Shop, Magelang.